Book Interactive For Mentally Disabled Children Short For Increase Ability Psychomotor and Needs Sensory and Cognitive Mentally Retarded Children - Sasqia Pratiwi Hanum AT; Anggie Pradina Azzahra; Ira Wirasari (Jipmor: Jurnal Ilmu Pendidikan Dan Humaniora, 2025)
Every human being has the same right to education, including children with intellectual disabilities. The abilities of these children can be explored and optimized through simple academic learning, such as reading, writing, and arithmetic. Therefore, children with intellectual disabilities should be provided with stimulation that can aid in their development and productivity, such as interactive books. Previous research has shown that interactive books are effective for typically developing children, and it is hoped that this learning medium can also be applied to children with intellectual disabilities. The research method used in this study is the design thinking method, with a particular focus on the empathize stage. Through a combination of observation, in-depth interviews, and questionnaires, this research aims to provide comprehensive insights into the learning needs of children with intellectual disabilities at SLB C Terate Bandung. The results of this study are expected to make a significant contribution to the development of more effective and suitable teaching methods and media for students with special needs. The findings indicate that interactive books are highly effective for the education of children with intellectual disabilities, with some adjustments needed in design and approach to meet their sensory and cognitive needs.